Pengaruh Kepemilikan Manajerial dan Investment Opportunity Set Terhadap Kebijakan Hutang Dengan Free Cash Flow Sebagai Variabel Moderasi - Siti Munajah; Dirvi Surya Abbas; Hustna Dara Sarra (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to examine the effect of managerial ownership and investment opportunity set on debt policy with free cash flow as a moderator in manufacturing companies in the health sub-sector listed on the IDX. The population in this study includes all manufacturing companies in the health sub-sector listed on the IDX in 2017 2021, totaling 40 companies. Based on the sampling technique with purposive sampling obtained a sample of 8 companies. The data analysis method in this study uses panel data.regression analysis with the Moderated Regression Analysis (MRA) test. The results of this study indicate that the investment opportunity set has an effect on debt policy, and managerial ownership has no effect on debt policy policies. Free cash flow as a moderator is not able to moderate managerial ownership, investment opportunity sets on debt policy, but Free cash flow as a moderator is able to moderate debt policy.